Type 2 Diabetes Mellitus can be Prevented in Tobacco Shop Workers - Fusté Bruzain, Mercedes; Roque Doval, Yamila; Rodríguez González, Roberto (My University, 2019)
The control of type 2 diabetes mellitus should be early and regular to prevent chronic complications and it represents a current global health problem. A descriptive observational study was conducted with 23 workers who present this condition in the cigar Factory of Camajuaní from January to September 2019, with the aim of preventing chronic complications in this type of patient. 70% of the diagnoses were made by blood glucose while fasting. The presence of chronic complications and concomitant diseases was detected, such as: Diabetic polyneuropathies, skin diseases and non-alcoholic steatohepatitis. It was detected by examinations indicated to check the health of the workers and a late diagnosis was made, in the presence of chronic complications. The need for prevention and health promotion work was evidenced by the factory reader, in order to avoid morbidity and expansion rates in workers.
Keywords: Type 2 diabetes mellitus; Morbidity; Mortality; Educación Médica; Diabetes Mellitus; Salud